From Shelter to Server: Conceptualizing the intersection of housing insecurity, digital accessibility, and language teaching and learning - Pentón Herrera, Luis Javier; Young, Christel (Colombian Applied Linguistics Journal, 2025)
Within the domain of applied linguistics, the intertwined challenges of housing insecurity and digital inaccessibility profoundly impact teaching and learning outcomes. This article elucidates the complex intersectionality of these real-world issues and their implications for language educators and learners. Despite the burgeoning recognition of technology’s role in modern pedagogy, a significant portion of students, especially those grappling with housing instability, confront the reality of digital inaccessibility. This duality not only impedes academic engagement and achievement but also accentuates psychosocial stressors. Drawing from comprehensive literature, the paper articulates the profound implications housing instability has on students’ well-being and academic trajectories, particularly in the digital age. It further elaborates on the underrepresented nuances of housing insecurity for both teachers and students within the specific realm of language teaching and learning. This manuscript introduces the triadic relationship among housing insecurity, digital accessibility, and language teaching and learning, culminating in a conceptual lens. This relationship evinces how housing insecurity often limits digital access, creating, in turn, barriers to effective language learning and teaching. Emphasizing an integrative approach, the paper concludes with pragmatic considerations for policy reformation, targeted research, and adaptive pedagogical practices, aiming to foster a more equitable, resilient, and inclusive language education ecosystem.